Host genetic influences on the anthelmintic efficacy of papaya-derived cysteine proteinases in mice - Luoga W.; Mansur F.; Stepek G.; Lowe A.; Duce I.R.; Buttle D.J.; Behnke J.M. (Cambridge University Press, 2024)
Eight strains of mice, of contrasting genotypes, infected with Heligmosomoides bakeri were studied to determine whether the anthelmintic efficacy of papaya latex varied between inbred mouse strains and therefore whether there is an underlying genetic influence on the effectiveness of removing the intestinal nematode. Infected mice were treated with 330 nmol of crude papaya latex or with 240 nmol of papaya latex supernatant (PLS). Wide variation of response between different mouse strains was detected. Treatment was most effective in C3H (905-993% reduction in worm counts) and least effective in CD1 and BALB/c strains (360 and 405%, respectively). Cimetidine treatment did not improve anthelmintic efficacy of PLS in a poor drug responder mouse strain. Trypsin activity, pH and PLS activity did not differ significantly along the length of the gastro-intestinal (GI) tract between poor (BALB/c) and high (C3H) drug responder mouse strains. Our data indicate that there is a genetic component explaining between-mouse variation in the efficacy of a standard dose of PLS in removing worms, and therefore warrant some caution in developing this therapy for wider scale use in the livestock industry, and even in human medicine. Copyright Cambridge University Press 2015.